Health and social service provider perspectives on challenges, approaches, and recommendations for treating long COVID: a qualitative study of Canadian provider experiences - Anh T. P. Nguyen; Chantal F. Ski; David R. Thompson; Susan E. Abbey; Stefan Kloiber; Natasha Yasmin Sheikhan; Peter Selby; Roslyn Shields; Susan L. Rossell; Gillian Strudwick; David Castle; Lisa D. Hawke (BMC Health Services Research)
Abstract Background Many people who contract the SAR-CoV-2 virus present with multiple persistent and debilitating physical, cognitive and mental health symptoms that endure beyond the acute infection period. This new syndrome – generally referred to as long COVID – negatively affects patients’ emotional wellbeing and quality of life, and presents a major challenge for treatment providers. Considering the lack of evidence-based treatment and supports, this qualitative descriptive study explores the experiences of Canadian health and social service providers working with individuals with long COVID, as well as their suggestions for intervention development. Methods Twenty health and social service providers between the ages of 29 and 57 across Canada completed virtual individual interviews to discuss their care experiences and service recommendations for long COVID. Participants were from a range of service sectors, including primary care, rehabilitation, mental health, and community support. Interviews were recorded, transcribed, and analyzed using codebook thematic analysis. Results Four themes illustrated providers’ the experiences of (1) selecting personalized treatments based on patient presentation and similar conditions amidst uncertainty; and their recommendations for long COVID services, including (2) building an integrated and evidence-based model of care; (3) providing holistic support for patients and families through psychoeducation and daily living resources; and (4) caring for mental health in long COVID. Conclusions Canadian health and social service providers are adopting personalized treatment approaches to address the symptom persistence of long COVID in the face of a considerable knowledge gap. A comprehensive, integrated care pathway is needed to support patients’ physical and psychosocial wellbeing while increasing provider preparedness to treat this complex condition.